Effects of syntaxin 2, 3, and 4 on rat and human epithelial sodium channel (ENaC) in Xenopus laevis oocytes - Rauh, Robert; Frost, Fabian; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

Effects of syntaxins 2, 3, and 4 on rat and human epithelial sodium channel (ENaC) in Xenopus laevis oocytes - Rauh, Robert; Frost, Fabian; Korbmacher, Christoph (Pflügers Archiv: European Journal of Physiology, 2020)
Syntaxins are SNARE proteins and may play a role in epithelial sodium channel (ENaC) trafficking. The aim of the present study was to investigate the effects of syntaxin 2 (STX2), syntaxin 3 (STX3), and syntaxin 4 (STX4) on rat (rENaC) and human ENaC (hENaC). Co-expression of rENaC and STX3 or STX4 in Xenopus laevis oocytes increased amiloride-sensitive whole-cell currents (Delta I-ami) on average by 50% and 135%, respectively, compared to oocytes expressing rENaC alone. In contrast, STX2 had no significant effect on rENaC. Similar to its effect on rENaC, STX3 stimulated hENaC by 48%. In contrast, STX2 and STX4 inhibited hENaC by 51% and 44%, respectively. Using rENaC carrying a FLAG tag in the extracellular loop of the beta-subunit, we demonstrated that the stimulatory effects of STX3 and STX4 on Delta I-ami were associated with an increased expression of the channel at the cell surface. Co-expression of STX3 or STX4 did not significantly alter the degree of proteolytic channel activation by chymotrypsin. STX3 had no effect on the inhibition of rENaC by brefeldin A, and the stimulatory effect of STX3 was preserved in the presence of dominant negative Rab11. This indicates that the stimulatory effect of STX3 is not mediated by inhibiting channel retrieval or by stimulating fusion of recycling endosomes. Our results suggest that the effects of syntaxins on ENaC are isoform and species dependent. Furthermore, our results demonstrate that STX3 increases ENaC expression at the cell surface, probably by enhancing insertion of vesicles carrying newly synthesized channels.
CRIS-Team WoS Importer:2020-04-07